F508del CFTR gene mutation in patients with allergic bronchopulmonary aspergillosis. (3rd August 2018) - Gamaletsou, Maria N.; Hayes, Gemma; Harris, Chris; Brock, Joanna; Muldoon, Eavan G.; Denning, David W.
ABSTRACT: Objective : The F508del mutation occurs in approximately 3.5% of Caucasian population of Northern Europe. Heterozygotes have increased risk for asthma and reduced pulmonary function. Allergic bronchopulmonary aspergillosis (ABPA) is more common in patients with cystic fibrosis (CF). We aimed to establish the frequency of F508del mutation in adult patients with ABPA. Methods : A retrospective matched case-control study of CF genotyped patients with ABPA seen at the National Aspergillosis Centre was undertaken. Key data were collected retrospectively from medical records, including respiratory comorbidities, total IgE, Aspergillus IgG and IgE, and immunoglobulins. Cystic fibrosis transmembrane regulator (CFTR) gene mutation analysis included multiplex PCR and sequencing. Results : From a cohort of 189 ABPA patients, 156 were screened for common mutations and variants in the CFTR gene. Eighteen were heterozygous for at least one CFTR mutation; 12 (7.7%) were heterozygous for the F508del, notably; 3 were heterozygous for the intron 8 5T variant; and 1 for an intronic variant of uncertain significance, c.3139 + 18C>T. Eight (67%) had asthma, 7 (58%) had CT-defined bronchiectasis, 4 (33%) hypergammaglobulinemia (>16 g/L), 3 (25%) sinusitis and 1 (8%) chronic pulmonary aspergillosis. Eight (67%) had elevated Aspergillus IgG antibodies (42–98 mg/L), and 8 (67%) had total IgE above 1, 000 KIU/L. Two individuals heterozygous for the F508del mutation and the TG12T5 variant were diagnosed with CF, leading to a de novo CF discovery rate of 1.3%. Conclusions : In our ABPA patient cohort, the presence of the delta F508 mutation was higher than that seen in general population. Genetic counseling for CFTR genotyping might be appropriate for these patients.